Multicenter Australian Trial of Islet Transplantation: Improving Accessibility and Outcomes. Issue 7 (13th May 2013) - O'Connell, P. J.; Holmes‐Walker, D. J.; Goodman, D.; Hawthorne, W. J.; Loudovaris, T.; Gunton, J. E.; Thomas, H. E.; Grey, S. T.; Drogemuller, C. J.; Ward, G. M.; Torpy, D. J.; Coates, P. T.; et al.
Abstract Whilst initial rates of insulin independence following islet transplantation are encouraging, long‐term function using the Edmonton Protocol remains a concern. The aim of this single‐arm, multicenter study was to evaluate an immunosuppressive protocol of initial antithymocyte globulin (ATG), tacrolimus and mycophenolate mofetil (MMF) followed by switching to sirolimus and MMF. Islets were cultured for 24 h prior to transplantation. The primary end‐point was an HbA1c of <7% and cessation of severe hypoglycemia. Seventeen recipients were followed for ≥12 months. Nine islet preparations were transported interstate for transplantation. Similar outcomes were achieved at all three centers. Fourteen of the 17 (82%) recipients achieved the primary end‐point. Nine (53%) recipients achieved insulin independence for a median of 26 months (range 7–39 months) and 6 (35%) remain insulin independent. All recipients were C‐peptide positive for at least 3 months. All subjects with unstimulated C‐peptide >0.2 nmol/L had cessation of severe hypoglycemia. Nine of the 17 recipients tolerated switching from tacrolimus to sirolimus with similar graft outcomes. There was a small but significant reduction in renal function in the first 12 months. The combination of islet culture, ATG, tacrolimus and MMF is a viable alternative for islet transplantation.